A single nucleotide polymorphism in the CYP4F2 but not CYP4A11 gene is associated with increased 20-HETE excretion and blood pressure - Ward, Natalie; Tsai, I.; Barden, A.; Van Bockxmeer, F.; Puddey, I.; Hodgson, J.; Croft, K. (American Heart Association, 2008)
Arachidonic acid is a major fatty acid that can be metabolized by the cytochrome P450 enzyme to a number of bioactive eicosanoids. A major metabolite of this oxidation is 20-hydroxyeicosatetraenoic acid, which acts as a potent vasoconstrictor. However, in the kidney, its vasoconstrictor actions can be offset by its natriuretic properties. A guanine-to-adenine polymorphism in the CYP4F2 gene was associated with a reduction in 20-hydroxyeicosatetraenoic acid production in vitro. A thymidine-to-cytosine polymorphism in the CYP4A11 gene reduced catalytic activity by >50% in vitro and was associated with hypertension. The aim was to determine whether these 2 mutations are associated with urinary 20-hydroxyeicosatetraenoic acid excretion and blood pressure in humans. For the CYP4F2, 51% were homozygous for the G allele, 40% were carriers, and 9% were homozygous for the A allele. For CYP4A11, 72% were homozygous for the T allele, 25% were carriers, and 3% were homozygous for the C allele. The CYP4F2 GA/AA genotype was significantly associated with an increase in both 20-hydroxyeicosatetraenoic acid excretion and systolic blood pressure. The CYP4A11 CC/TC genotype was significantly associated with a reduction in 20-hydroxyeicosatetraenoic acid excretion but was not associated with blood pressure. We have demonstrated for the first time in humans that polymorphisms of the CYP4F2 and CYP4A11 genes have opposite effects on 20- hydroxyeicosatetraenoic acid excretion. The positive association between the CYP4F2 GA/AA genotype and both systolic blood pressure and 20- hydroxyeicosatetraenoic acid excretion strengthens a role for 20-hydroxyeicosatetraenoic acid in the modulation of blood pressure. © 2008 American Heart Association, Inc.